IN SILICO DOCKING APPROACH FOR ANTIATHEROSCLEROTIC ACTIVITY OF PHYTOCONSTITUENTS OF CORCHORUS AESTUANS AND ADMET PREDICTION - R, Dhanalakshmi; MANAVALAN R, (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: Atherosclerosis is a persistent inflammatory condition within the arterial wall characterized by alterations in lipid metabolism. Liver X alpha receptor is highly expressed in liver could regulate the cholesterol metabolism and suppress the inflammatory genes, so that its activation prevents atherosclerosis. The Corchorus aestuans possess anti-atherosclerotic property along with its anti-hyperglycemic activity. The objective of the present study is to investigate the anti-atherosclerotic activity of the C. aestuans leaves against Liver X alpha receptor by using GOLD study. Methods: 3-Dimensional structure of Liver X alpha receptor (Protein Date Bank ID - 3IPQ) was retrieved using Protein Data Bank. Phytochemical molecules were retrieved from the pubchem database and the 2D chemical structures were generated from SMILES notation (Simplified Molecular Input Line Entry Specification) by using the Chemsketch Software. Screenings of different docked complex were performed by GOLD study. Absorption, distribution, metabolism, excretion and toxicity properties for all molecules is predicted by using ADMET structure-activity relationship database. Results: Among the 14 phytochemicals, E-7-Tetradecenol was found to be the top compound with highest Gold score of 26.99. Conclusion: Our study suggests that phytochemicals from C. aestuans leaves may act as better leads and in turn prevent atherosclerosis. Keywords: Atherosclerosis, Corchorus aestuans, Liver X alpha receptor, GOLD, Absorption, Distribution, Metabolism, Excretion and Toxicity.